History of the Kansas State Agricultural College - Walters, John Daniel, 1847-1929. (Kansas State College Press, 2015)
It will soon be half a century since the Kansas State Agricultural College was founded and located. For a new State, and one that made history as fast as the trans-Missourian countries did, this is a long period. Many of the men to whose efforts the people of Kansas owe this magnificent institution of learning—the largest school of its kind in America—have left to conquer other territories, some have followed more remunerative callings than that of the educator, and many have died. The semi-centennial now close at hand will find but few of the pioneers in health and vigor. If a history including the valuable element of personal recollection was to be written, the work could not be deferred much longer. This volume is really a fifth revised and enlarged edition of an historic monograph originally written by the author for the Riley County Map Book, published in 1881. The second sketch was written for the U. S. Bureau of Education in 1890. The third was published as a 76 page pamphlet, entitled "Columbian History of the Kansas State Agricultural College," of which a special edition of 4000 copies was distributed at the Columbian Exposition at Chicago in 1893, and the fourth appeared as a contribution to volume VII of the Transactions of the Kansas State Historical Society. Each succeeding effort meant a considerable increase in pages and a more complete and correct representation of the facts. These historic sketches were read by many who "had been there," and there were all kinds of comments. The author expects that there will be exceptions to some of the statements in this volume, but, whatever the criticisms may be, he can say that he has told the story as he saw it, that he has tried to be clear and concise, and that he has verified uncertain data by comparing them with the publications and archives of the College, the files of the newspapers of Manhattan, and the collections of the Kansas State Historical Society. Considerable space has been reserved for chronological tables and law quotations. It is hoped that while those paragraphs are dry reading they will be found valuable as references. The author regrets that the available time fragments which he devoted to work on this volume did not permit the publication of the biographies of a much larger number of the "Makers of the College." The book should contain the life stories of at least a hundred educators and public men, who contributed their best efforts to found and rear the great technical school at Manhattan, in place of only thirty-three. It should preserve for the future Kansan the character sketches of Governors Harvey and Green, Reverend Reynolds, Gen. J. K. Hudson, Regents Forsyth, Lemmon, Adams, Purcell, Secrest, J. Wheeler, R. P. Kelley, Hoffman, etc., and of Professors Miller, Detmers, Platt, A. Todd, A. A. Stewart, Hood, Mason, Brown, White, Mayo, Otis, Erf, Burkett, and many others, not to mention a score or more who are still at work on the grand structure whose foundation was laid half a century ago by Senator Justin A. Morrill, of Vermont. May a sharper pen—one less hampered by a lengthy program of daily routine tasks—extend the work outlined in these pages, and gather up the interesting material before it is distorted by time or entirely lost. History begets loyalty and patriotism. --Manhattan, May 1909. J. D. WALTERS.
Call number: S537.K39 W5
Keywords: Kansas State University; Institution history; Kansas State Agricultural College; State universities (institutions); State colleges (institutions); Rare books